Build the Read: A Hands-On Activity for Introducing Microbiology Students to Next-Generation DNA Sequencing and Bioinformatics - Guerrino Macori (American Society for Microbiology, 2017)
Next-Generation Sequencing (NGS) is the current standard for providing genomic data, by virtue of the ability of the technology to generate a considerable amount of information rapidly and at low cost. The data generated can be of key importance to research and addressing issues in public health and, thus, is relevant to society. Unsurprisingly, content relating to the principle and chemistry underlying Next-Generation Sequencing is presented to almost every microbiology-related class, to professionals across multiple fields and, to the general public as popular science. The most commonly utilized NGS platforms (MiSeq, NextSeq and HighSeq) are those provided by Illumina. In this paper, we describe a hands-on activity for students to represent the chemistry underlying Illumina-based NGS, by creating representative reads using LEGO blocks, to link indexes, assemble the sequence and ‘identify’ the bacteria from which the DNA originated, thereby, in the process introducing the participants to the basic principles of bioinformatics.